Localization: An Adaptive Transitional Process for Leadership Capability Development in a Multi-local company - Sinhaseni, Narumol (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
This paper explores leadership theories and cultural dimensions for local leadership development in Multi Nationals Companies (MNCs) in Thailand. It focuses on cultural differences between Thailand and Germany as the subject of discussion related to Siemens Limited Thailand only. The cultural studies range from Thai history that shapes the Thai culture and the education development in the countr y that have direct impact on local leadership styles and capabilities. The MNCs have to develop themselves to be more localized by understanding local cultures that have rooted in each local individual to develop leaders for the organization, which is now perceived more as Multi Local Companies (MLCs) than MNCs. This paper suggests that when cultural synergies are utilized and a specific local leadership development plan is prepared, a higher success rate of foreign companies investing in Thailand in both business and social perspectives is ensured.